PEMBUATAN VISUM ET REPERTUM OLEH DOKTER SEBAGAI UPAYA MENGUNGKAP PERKARA DI DALAM PROSES PERADILAN - HANGSI PRIYANTO (MIH Unsoed, 2019)
The making of Visum et Repertum gives full duty to doctors as implementers in the field to assist prosecutors in determining the direction of the charges that will be charged against the defendant, as well as assisting the judge in finding material truth in deciding criminal cases. This research is aimed at knowing and analyzing the technique of making Visum et Repertum by doctors as an effort to uncover cases in the judicial process. In addition, it is also intended to find out the authority to make Visum et Repertum by forensic experts and analyze the role of Visum et Repertum for judges in disclosing cases in the judicial process. The study uses a normative juridical approach, with secondary data sources.The results showed that the technique of making Visum et Repertum by doctors as an effort to uncover cases in the judicial process was divided into techniques which were examination of wounded victims, techniques for examining sexual crime victims, child victim examination techniques, extermination examination techniques and autopsies and psychiatric examination techniques. Visum et Repertum (VeR) was made at the request of the National Police investigator through an official letter signed at least by the Sector Police Chief. Visum et Repertum does not have to be made by a forensic specialist. The subjects making visum et repertum in the judicial process are also distinguished on the division of abilities, namely by the specialization stipulated in the legislation and the subject of general visum et repertum makers. The role of Visum et Repertum for judges in disclosing cases in the judicial process is the completeness of evidence in pro-judicial cases with examinations in court proceedings, assisting in efforts to increase the judge's confidence in decision making.